Co-localization and crosstalk between CD44 and RHAMM depend on hyaluronan presentation - Carvalho, Ana Margarida Moura Pereira Ferreira (2021)
CD44 and the receptor for hyaluronic acid-mediated motility (RHAMM) are the main hyaluronan (HA) receptors. They are commonly overexpressed in different cancers activating signaling pathways related to tumor progression, metastasis and chemoresistance. Besides their involvement in signal transduction via interaction with HA, currently, there is a little information about the possible crosstalk between CD44 and RHAMM and the role of HA in this process. In the present work, we used immunocytochemistry combined with Förster resonance energy transfer (FRET) microscopy and co-immunoprecipitation to elucidate the involvement of HA in CD44 and RHAMM expression, co-localization and crosstalk. We studied breast cancer cells lines with different degrees of invasiveness and expression of these receptors in the absence of exogenous HA and compared the data with the results obtained for cultures supplemented with either soluble HA or seeded on substrates with end-on immobilized HA. Our results demonstrated that cells response depends on the HA presentation: CD44/RHAMM complexation was upregulated in all cell lines upon interaction with immobilized HA, but not with its soluble form. Moreover, the results showed that the expression of both CD44 and RHAMM is regulated via interactions with HA indicating cell-specific feedback loop(s) in the signaling cascade.